Respuesta :
Use the product rule to differentiate the first function:
[tex]g(x)=f(x)\sin x\implies g'(x)=f'(x)\sin x+f(x)\cos x[/tex]
which means
[tex]g'\left(\dfrac\pi3\right)=f'\left(\dfrac\pi3\right)\sin\dfrac\pi3+f\left(\dfrac\pi3\right)\cos\dfrac\pi3=2-\sqrt3[/tex]
Now use quotient rule for the second one.
[tex]h(x)=\dfrac{\cos x}{f(x)}\implies h'(x)=\dfrac{-f(x)\sin x-f'(x)\cos x}{f(x)^2}[/tex]
so you have
[tex]h'\left(\dfrac\pi3\right)=\dfrac{-f\left(\dfrac\pi3\right)\sin\dfrac\pi3-f'\left(\dfrac\pi3\right)\cos\dfrac\pi3}{f\left(\dfrac\pi3\right)^2}=\dfrac1{16}-\dfrac{\sqrt3}8[/tex]
[tex]g(x)=f(x)\sin x\implies g'(x)=f'(x)\sin x+f(x)\cos x[/tex]
which means
[tex]g'\left(\dfrac\pi3\right)=f'\left(\dfrac\pi3\right)\sin\dfrac\pi3+f\left(\dfrac\pi3\right)\cos\dfrac\pi3=2-\sqrt3[/tex]
Now use quotient rule for the second one.
[tex]h(x)=\dfrac{\cos x}{f(x)}\implies h'(x)=\dfrac{-f(x)\sin x-f'(x)\cos x}{f(x)^2}[/tex]
so you have
[tex]h'\left(\dfrac\pi3\right)=\dfrac{-f\left(\dfrac\pi3\right)\sin\dfrac\pi3-f'\left(\dfrac\pi3\right)\cos\dfrac\pi3}{f\left(\dfrac\pi3\right)^2}=\dfrac1{16}-\dfrac{\sqrt3}8[/tex]
Following are the calculation to the given question:
Given:
[tex]\bold{f(\frac{\pi}{3})=4} \\\\\bold{f'(\frac{\pi}{3})= -2} \\\\\bold{g(x)=f(x)\ \sin x}\\\\\bold{h(x)=\frac{\cos x}{f(x)}}[/tex]
To find:
[tex]\bold{g'(\frac{\pi}{3})=?} \\\\ \bold{h'(\frac{\pi}{3})=?}[/tex]
Solution:
[tex]\bold{g(x) = f(x)\times \sin(x)}[/tex]
Calculating the derivative with the respect of x:
[tex]\bold{g'(x) = f'(x)\times \sin(x) + f(x)\times \cos(x)}[/tex]
at [tex]\ \bold{x =\frac{\pi}{3}}[/tex]
[tex]\to \bold{g'(\frac{\pi}{3}) = f'(\frac{\pi}{3})\times (\frac{\sqrt{3}}{2}) +f(\frac{\pi}{3})\times(\frac{1}{2})}\\\\[/tex]
Calculating the value for all values of "n" [tex]f(\frac{n}{3}) = 4[/tex] and [tex]f'(\frac{n}{3}) =-2[/tex]:
Therefore
[tex]\to g'(x) = (-2)\times (\frac{\sqrt{3}}{2}) + 4\times (\frac{1}{2})\\\\\to g'(x) = -\sqrt{3} + 2\\\\Now,\\\\\to h(x) = \frac{cos(x)}{f(x)}[/tex]
Derivative with the respect of x:
[tex]\to \bold{h'(x) = \frac{[- \sin(x)\times f(x) +f'(x)\times cos(x)]}{[f(x)]^2}}\\\\[/tex]
at [tex]\bold{x =\frac{\pi}{3}}[/tex]
[tex]\to h'(\frac{pi}{3}) = [(-\frac{\sqrt{3}}{2})\times 4 + \frac{(-2)\times (\frac{1}{2})]}{[4]^2}\\\\\to h'(\frac{pi}{3}) = \frac{[-\frac{\sqrt{3}}{2} -1]}{16}\\\\\to h'(\frac{pi}{3}) = -\frac{(2+\sqrt{3})}{32}[/tex]
Learn more:
brainly.com/question/3436083